2004
DOI: 10.1002/ajpa.20111
|View full text |Cite
|
Sign up to set email alerts
|

Continuity or colonization in Anglo‐Saxon England? Isotope evidence for mobility, subsistence practice, and status at West Heslerton

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 52 publications
(42 reference statements)
7
94
0
Order By: Relevance
“…This phenomenon is attributed to high levels of exposure occurring with lead-rich anthropogenic sources with a limited isotopic range, and low levels of exposure deriving from isotopically-diverse natural sources. This inverse correlation of isotopic ratio with concentration has therefore been termed "cultural focussing" (Montgomery et al 2005).On the basis of a visual inspection of a similar figure, Montgomery et al (2010:212) suggested that lead concentrations in excess of about 0.5 ppm should be regarded as having an anthropogenic component as this is the point at which cultural focussing becomes apparent. Here we extend the analysis with a more formal investigation to define a suitable cut-off point above which we regard the lead content of human tooth enamel to have an undoubted technological contribution.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is attributed to high levels of exposure occurring with lead-rich anthropogenic sources with a limited isotopic range, and low levels of exposure deriving from isotopically-diverse natural sources. This inverse correlation of isotopic ratio with concentration has therefore been termed "cultural focussing" (Montgomery et al 2005).On the basis of a visual inspection of a similar figure, Montgomery et al (2010:212) suggested that lead concentrations in excess of about 0.5 ppm should be regarded as having an anthropogenic component as this is the point at which cultural focussing becomes apparent. Here we extend the analysis with a more formal investigation to define a suitable cut-off point above which we regard the lead content of human tooth enamel to have an undoubted technological contribution.…”
Section: Resultsmentioning
confidence: 99%
“…Due to shared chemical similarities, strontium isotopes readily substitute for calcium in the skeleton and are integrated into the bioapatite of bone and teeth. This relationship between geology and skeletal chemistry has been exploited in provenance studies from a wide range of geographical contexts (e.g., Sealy et al, 1995;Ezzo et al, 1997;Beard and Johnson, 2000;Price et al, 2000;Montgomery et al, 2005). The strontium isotope abundance most commonly analyzed in human and animal skeletal material is the radiogenic 8 7 S r , which is normalized against the nonradiogenic 8 6 S r , cancelling out variations in total strontium (Budd et al, 2004;Bentley, 2006).…”
Section: Identifying Past Mobility Using Stable Isotope Analysesmentioning
confidence: 99%
“…Although geologists initially used the natural variation of strontium isotopes in the environment to date igneous and sedimentary rocks, researchers in archaeology, biology, geology and paleontology have begun to utilize the fact that different geologic environments have different strontium isotope ratios to answer a wide variety of questions, such as the identification of animal migration pat-terns (Hoppe 2004;Hoppe et al 1999;Ingram and Weber 1999;Kennedy et al 1997). However, most strontium isotope analyses in archaeology have been used to answer questions about human migration (Bentley 2006;Bentley et al 2003;Bentley et al 2002;Ezzo et al 1997;Ezzo and Price 2002;Farnum et al 2003;Grupe et al 1997;Knudson 2004;Knudson et al 2004;Montgomery et al 2003;Montgomery et al 2005;Price et al 2001;Price et al 1998;Price et al 1994;Price et al 2000;Price et al 2006;Schweissing and Grupe 2003a, b;Sealy et al 1995;Sealy et al 1991;Sillen et al 1998;Wright 2005a, b).…”
Section: Archaeological Chemistry and Human Remainsmentioning
confidence: 99%